Definition and Validation of Requirements for Collaborative Decision-Making in Enterprise Architecture Creation - Nakakawa, Agnes; Van Bommel, Patrick; Proper, H. A. Erik (International Journal of Cooperative Information Systems, 2011)
Gartner advises that for enterprise architecture development to be successful, it is vital that enterprise architects ensure effective communication and also form virtual teams that create and agree on enterprise architecture content. One of the ways to achieve this is to enforce Collaborative Decision Making (CDM) during enterprise architecture creation. Guided by Design Science, we are developing a method referred to as Collaborative Evaluation of (Enterprise) Architecture Design Alternatives (CEADA) to enable CDM during enterprise architecture creation. The method attempts to resolve challenges in enterprise architecting that are caused by ineffective collaboration between enterprise architects and organizational stakeholders. Requirements for CEADA have been defined based on the causality analysis theory, the generic decision-making process, enterprise architecture frameworks (and literature), and the CDM theory. In addition, Collaboration Engineering has been used to design a collaboration process to address these requirements. Models describing the requirements and the design of the collaboration process, have been evaluated using the analytical, experimental, and observational methods. This paper discusses the implications of findings from these evaluations and presents the validated requirements for realizing CDM in enterprise architecture creation. Thus, this research generally attempts to strengthen enterprise architecting guidelines with collaborative activities, so as to enable effective execution of collaboration-dependent tasks.
Keywords: Enterprise architecture; Collaborative decision making